Ultrasensitive detection of SARS-CoV-2 spike protein by graphene field-effect transistors. Issue 3 (22nd December 2022) - Silvestri, Alessandro; Zayas-Arrabal, Julian; Vera-Hidalgo, Mariano; Di Silvio, Desire; Wetzl, Cecilia; Martinez-Moro, Marta; Zurutuza, Amaia; Torres, Elias; Centeno, Alba; Maestre, Arantxa; Gómez, Juan Manuel; Arrastua, María; et al.
Abstract : By finely controlling the graphene functionalisation, by tuning the Debye length, and by deeply characterising the ACE2-spike protein interactions, we have been able to detect SARS-CoV-2 spike protein with an extremely low limit of detection. Abstract : COVID-19, caused by the severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2), originated a global health crisis, causing over 2 million casualties and altering human daily life all over the world. This pandemic emergency revealed the limitations of current diagnostic tests, highlighting the urgency to develop faster, more precise and sensitive sensors. Graphene field effect transistors (GFET) are analytical platforms that enclose all these requirements. However, the design of a sensitive and robust GFET is not a straightforward objective. In this work, we report a GFET array biosensor for the detection of SARS-CoV-2 spike protein using the human membrane protein involved in the virus internalisation: angiotensin-converting enzyme 2 (ACE2). By finely controlling the graphene functionalisation, by tuning the Debye length, and by deeply characterising the ACE2-spike protein interactions, we have been able to detect the target protein with an extremely low limit of detection (2.94 aM). This work set the basis for a new class of analytical platforms, based on human membrane proteins, with the potential to detect a broad variety of pathogens, even before their isolation, being a powerful tool in the fight against future pandemics.